Re: What's wrong with this assuming?
- To: mathgroup at smc.vnet.net
- Subject: [mg111121] Re: What's wrong with this assuming?
- From: Sam Takoy <sam.takoy at yahoo.com>
- Date: Wed, 21 Jul 2010 07:11:52 -0400 (EDT)
- References: <i242rv$opo$1@smc.vnet.net>
Thanks for all this response and all that haven't showed up on the newsgroup yet. Here's my actual problem: Assuming[ a Cosh[H/(2 a)] == 1, FullSimplify[ Cosh[H/a] + 1/2 ((H/a - H/a Cosh[H/a] + 2 Sinh[H/a]) Sinh[H/(2 a)] )/( H/(2 a) Sinh[H/(2 a)] - 1/a)]] and the answer is "1"; My version of Mathematica (7) fails to do this simplification. Thanks again! On 7/20/2010 7:55 AM, Bob Hanlon wrote: > Use the assumption directly in Simplify or FullSimplify > > Simplify[(x^2 + x)^2 + h, x^2 + x == h] > > h (h+1) > > FullSimplify[(x^2 + x)^2 + h, x^2 + x == h] > > h (h+1) > > Or put Simplify or FullSimplify within the scope of the Assuming construct > > Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]] > > h (h+1) > > Assuming[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h]] > > h (h+1) > > > Bob Hanlon > > ---- Sam Takoy<sam.takoy at yahoo.com> wrote: > > ============= > Hi, > > > I have a situation where I have to simplify an expression that contains > x and h, but x is given implicitly by h, so I can't explicitly eliminate > it. So here's a simpler example that I'm trying and it does nothing: > > Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify > > Is there a way to make this work? > > Thanks! > > > -- > > Bob Hanlon > >